Development and validation of the Dynamic Collimation Monte Carlo simulation package for pencil beam scanning proton therapy. Issue 6 (9th April 2021) - Nelson, Nicholas P.; Culberson, Wesley S.; Hyer, Daniel E.; Geoghegan, Theodore J.; Patwardhan, Kaustubh A.; Smith, Blake R.; Flynn, Ryan T.; Yu, Jen; Rana, Suresh; Gutiérrez, Alonso N.; Hill, Patrick M.
Abstract : Purpose: The aim of this work was to develop and experimentally validate a Dynamic Collimation Monte Carlo (DCMC) simulation package specifically designed for the simulation of collimators in pencil beam scanning proton therapy (PBS‐PT). The DCMC package was developed using the TOPAS Monte Carlo platform and consists of a generalized PBS source model and collimator component extensions. Methods: A divergent point‐source model of the IBA dedicated nozzle (DN) at the Miami Cancer Institute (MCI) was created and validated against on‐axis commissioning measurements taken at MCI. The beamline optics were mathematically incorporated into the source to model beamlet deflections in the X and Y directions at the respective magnet planes. Off‐axis measurements taken at multiple planes in air were used to validate both the off‐axis spot size and divergence of the source model. The DCS trimmers were modeled and incorporated as TOPAS geometry extensions that linearly translate and rotate about the bending magnets. To validate the collimator model, a series of integral depth dose (IDD) and lateral profile measurements were acquired at MCI and used to benchmark the DCMC performance for modeling both pristine and range shifted beamlets. The water equivalent thickness (WET) of the range shifter was determined by quantifying the shift in the depth of the 80% dose point distal to the Bragg peak between the range shifted and pristine uncollimated beams. Results: A source model of the IBA DN system was successfully commissioned against on‐ and off‐axis IDD and lateral profile measurements performed at MCI. The divergence of the source model was matched through an optimization of the source‐to‐axis distance and comparison against in‐air spot profiles. The DCS model was then benchmarked against collimated IDD and in‐air and in‐phantom lateral profile measurements. Gamma analysis was used to evaluate the agreement between measured and simulated lateral profiles and IDDs with 1%/1 mm criteria and a 1% dose threshold. For the pristine collimated beams, the average 1%/1 mm gamma pass rates across all collimator configurations investigated were 99.8% for IDDs and 97.6% and 95.2% for in‐air and in‐phantom lateral profiles. All range shifted collimated IDDs passed at 100% while in‐air and in‐phantom lateral profiles had average pass rates of 99.1% and 99.8%, respectively. The measured and simulated WET of the polyethylene range shifter was determined to be 40.9 and 41.0 mm, respectively. Conclusions: We have developed a TOPAS‐based Monte Carlo package for modeling collimators in PBS‐PT. This package was then commissioned to model the IBA DN system and DCS located at MCI using both uncollimated and collimated measurements. Validation results demonstrate that the DCMC package can be used to accurately model other aspects of a DCS implementation via simulation.